2014
DOI: 10.4028/www.scientific.net/amr.911.326
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Methyl Violet Dye from Aqueous Solutions by Activated Carbon Produced from Tamarind Seeds

Abstract: The present work proposes the adsorption of methyl violet (MV) from two solution systems including single MV and binary MV-Cu2+systems by activated carbon (AC) prepared from tamarind seeds in a batch system. Parameters including contact time, solution pH, adsorbent dose, and initial dye concentration were studied. The morphology of the AC was determined by scanning electron microscopy (SEM). The results showed the maximum adsorption of MV dye onto the AC at a contact time of 60 min, solution pH of 9.0 and adso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Adsorption isotherms. Adsorption isotherms can provide information on the interactions between adsorbate and adsorbent, which is helpful when trying to optimize the use of adsorbent 35 . Langmuir, Freundlich, and Temkin isotherm models were chosen to evaluate the p-nitrophenol adsorption process (Fig.…”
Section: Factors That Impact P-nitrophenol Adsorption Effect Of Adsomentioning
confidence: 99%
“…Adsorption isotherms. Adsorption isotherms can provide information on the interactions between adsorbate and adsorbent, which is helpful when trying to optimize the use of adsorbent 35 . Langmuir, Freundlich, and Temkin isotherm models were chosen to evaluate the p-nitrophenol adsorption process (Fig.…”
Section: Factors That Impact P-nitrophenol Adsorption Effect Of Adsomentioning
confidence: 99%
“…hours and before activating, the samples were made sure to be in a semidried condition. Then, the samples underwent the activation process at 500 °C for four hours in muffle furnace to remove the non-carbonaceous components [21]. Lastly, the samples was washed with deionized water and 1.0 M of sodium hydroxide (NaOH) using vacuum filtration until the pH of the sample is neutral [22].…”
Section: Effect Of Temperaturementioning
confidence: 99%
“…Adsorbents made from raw or processed agro-waste can be used to remove of MV. Date Seeds MV 59.50 [47] Sawdust AC MV 531.16 [48] Waste Paper MV 4.30 [49] Granulated Mesoporus Carbon MV 202.80 [50] Coconut Husk Powder MV 454.54 [51] Sugarcane Bagasse MV 107.50 [52] Coffee Husks MV 12.24 [53] Blue Green Algae MV 13.41 [54] Peanut Husk MV 20.95 [55] Ceiba Pentandra Sawdust MV 15.33 [56] Kaolin MV 74.03 [57] Modified Palm Fiber MV 529.76 [58] Corn-Cob AC MV 40.81 [59] Raw Carobs MV 9.80 [60] Modified Carobs MV 62.50 [60] Tea Waste NPS MV 200.00 [61] Lemon Wood AC MV 23.60 [62] Tamarind Seeds AC MV 18.58 [63] Morocco MV 625.00 [64] Brown Algae MV 10.02 [65] Cardboard Waste MV 78.12 [66] The treatment of water and wastewater, as well as the management of waste, can benefit from the utilization of agricultural waste as adsorbents. It has been demonstrated that using agricultural waste as adsorbents is beneficial.…”
Section: Agro-waste: Potential Low-cost Adsorbentsmentioning
confidence: 99%
“…Industrial wastewater pollutant separation chemical engineering procedures include adsorption. Adsorption experiments using different adsorbents are described in depth in column/continuous adsorption studies, whereas batch adsorption studies give crucial information and parameters for removing dyes [63,75]. The parameters that will be adapted for use on an industrial scale employing fixed bed columns can be learned through experiments conducted on a smaller scale as part of the batch research [33,56].…”
Section: Batch Mode: Adsorptionmentioning
confidence: 99%